ANALISIS TANTANGAN PEMANFAATAN ALAT DIGITAL DALAM PENDIDIKAN PADA ANAK YANG CENDERUNG MENGHABISKAN WAKTU UNTUK GAME ONLINE DI MI AT-TARBIYAH SUMBERASIH - Akhmad Lutfi; Prasetiya, Benny (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to analyze the challenges of using digital tools in education for children who tend to spend time playing online games at MI AT-Tarbiyah Banjarsari, Banjarsari District. Sumberasih. In the digital era, the use of digital tools in learning is becoming increasingly important. However, children's tendency to spend time playing online games can be a barrier to the effective use of digital tools in educational settings. This research method uses a qualitative approach with data collection techniques through observation, interviews and documentation studies. The research subjects were teachers, parents and students of MI AT-Tarbiyah Banjarsari District. Sumberasih has a tendency to spend time playing online games. The research results show that there are several challenges in using digital tools in children's education at MI AT-Tarbiyah Banjarsari. Factors such as parents' lack of understanding of the benefits of digital tools in education, limited access to technology, and the strong appeal of online games are the main obstacles. This research recommends the need to increase parents' understanding of the benefits of digital tools in education, the active involvement of teachers in developing interesting educational content, and the development of school policies that support the positive use of digital tools. In this way, it is hoped that we can overcome challenges and increase the effectiveness of the use of digital devices in improving the quality of education for children who tend to spend time playing online games.